THE IDENTITY OF THE TRAFFICKED CHILD IN YOUNG ADULT LITERATURE: PATRICIA MCCORMICK’SOLD - Faisal Lafee Alobeytha; Abdul Halim Mohamed; Faizahani Ab Rahman, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This paper intends to do these followings; i) examine the effect of child sex trafficking on the identity of the trafficked child and ii) compare between the identity of the trafficked child before and during the child sex trafficking. For these purposes, Patricia McCormick’ Sold (2006) is selected to be studied in this paper. This paper employs a Bronfenbrenner’s Ecological System Theory (1994) as the framework of the study. Thematic approach of Braun and Clarke (2006) is used to analyze this literary text. The study finds that (i) child traffickers often try to erase the identity of the trafficked children and replace it with the identity of a slave or a prostitute, (ii) they follow different types of violence such as physical and psychological abuse to destroy the original identity of the trafficked children, (iii) the ecological systems contribute to the development of identities of children and (iv) young adult literature is an appropriate literature to discuss adolescents’ issues.